2005
DOI: 10.1038/sj.gt.3302459
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia reduces adenoviral replication in cancer cells by downregulation of viral protein expression

Abstract: Successful cancer therapy using replicating viral vectors relies on the spread of virus from infected to uninfected cells. To date, there has been limited clinical success in the use of replicating adenoviruses. In animal models, established xenograft tumors are rarely eliminated despite the persistence of high viral titers within the tumor. Hypoxia is a prevalent characteristic of solid tumors, whereas adenovirus naturally infects tissues exposed to ambient oxygen concentrations. Here, we report that hypoxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
70
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 29 publications
(47 reference statements)
0
70
0
1
Order By: Relevance
“…36 In this context, our group has recently shown that hypoxia impairs viral replication, and the hypoxic environment within the center of a tumor may be a contributing factor to the insufficiency of viral spread. 51 Clearly, the specific mechanisms that restrict viral spread need to be further elucidated. However, transgene expression or other modifications that lead to more rapid and effective tumor cell lysis are valuable option to improve viral spread and oncolytic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…36 In this context, our group has recently shown that hypoxia impairs viral replication, and the hypoxic environment within the center of a tumor may be a contributing factor to the insufficiency of viral spread. 51 Clearly, the specific mechanisms that restrict viral spread need to be further elucidated. However, transgene expression or other modifications that lead to more rapid and effective tumor cell lysis are valuable option to improve viral spread and oncolytic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…75 In recent studies, we have shown that the alcohol form of PR-104 is also an excellent substrate for NTR and displays marked activity in the WiDr mixed tumor model. Given the observations that hypoxia is an impediment to CRAd replication 85,86 and a common feature of solid tumors, 87 the independent co-activation of PR-104 by hypoxia and NTR may be of significant therapeutic value. We are currently evaluating whether PR-104 provides efficacy similar to SN 28343 in combination with ONYX-411 NTR and thus whether it has potential clinical utility in this context.…”
Section: Discussionmentioning
confidence: 99%
“…27,31 Moreover, considering the variety of pathways that have been linked to the loss of CAR in cancers, 8,[21][22][23] our data do also underline the need for modified adenoviruses that bind to the cell surface independently of CAR in novel concept for cancer treatment. 32 Abbreviations CAR, coxsackie and adenovirus receptor; TJ, tight junctions; HIF-1a, hypoxia-inducible factor-1a; FCS, fetal calf serum; GFP, green fluorescent protein . …”
Section: Discussionmentioning
confidence: 99%